Narrowing of airway caused by ingestion of methyl ethyl ketone peroxide - Bozdemir, M. N.; Yildiz, M.; Seyhanli, E. S.; Gurbuz, S.; Kilicaslan, I.; Karlidag, T. (Sage Publications Ltd, 2011)
Although ingestion of methyl ethyl ketone peroxide (MEKP) is rare, it carries a high risk of morbidity and mortality. This paper reports the first such case from Turkey in which a 70-year-old man unintentionally ingested MEKP in his kitchen. The patient was brought into the emergency department (ED) within I hour of ingestion, with the symptoms of sore throat, shortness of breath, nausea and vomiting. Visual examination of the oropharynx revealed minor burns and uvular edema. A laryngoscope examination performed in the ED showed superficial mucosal injury with edema of the oropharynx, uvula, posterior pharynx, epiglottis, arytenoids and vocal cords. Lateral cervical radiography revealed a narrowing of airway due to a thickened epiglottis. After the diagnostic evaluation was completed, the patient was admitted to the gastroenterology intensive care unit for monitoring of adverse reactions. During follow-up, the patient made an uneventful recovery. Ingestion of MEKP generally results from accidental ingestion from a container. Therefore, these containers should be kept in safe places. In addition, the priority following the ingestion of MEKP should be given to maintain open and adequate airway in the ED.
Keywords: methyl ethyl ketone peroxide; poisoning; laryngoscope; edema of vocal cords